Prevalence of potentially inappropriate prescribing among older adults: A comparison of the Beers 2012 and Screening Tool of Older Person's Prescriptions criteria version 2 - TUFAN ÇİNÇİN, ASLI (WILEY, 2017)
AimTo date, there is no study comparing the Beers 2012 and Screening Tool of Older Person's Prescriptions (STOPP) version 2 criteria, nor reporting a comparison of the prevalence of potentially inappropriate Prescribing (PIM) with STOPP version 2. We aimed to evaluate the prescriptions of patients admitted to a geriatric outpatient clinic with these tools, and to document the factors related to PIM use. MethodsOlder patients (aged 65 years) admitted to the outpatient clinic of a university hospital were retrospectively evaluated for PIM with Beers 2012 and STOPP version 2 criteria. Age; sex; chronic disease and number of drugs; and functional, depression and nutritional statuses were studied with regression analysis as possible factors related to PIM. ResultsThe study included 667 participants (63.1% women, mean age 77.6 6.3 years). The mean number of drugs was 6.1 +/- 3.4. PIM prevalence detected by STOPP version 2 was higher than that of the Beers 2012 criteria (39.1% vs 33.3%, respectively; P < 0.001; Z = -3.5) with moderate agreement in between (kappa = 0.44). Antipsychotics, over-the-counter vitamin/supplements, aspirin, selective-serotonin-reuptake-inhibitors and anticholinergics were the leading drug classes for PIM. The extent of polypharmacy (P < 0.001, OR 1.29, 95% CI 1.20-1.38) was the most important variable related to PIM, along with the multiple comorbidities (P = 0.005, OR 1.16, 95% CI 1.05-1.30). Higher level of functionality was inversely associated with PIM (P = 0.009, OR 0.90, 95% CI 0.83-0.97). ConclusionsInappropriate prescription prevalence of similar to 40% by STOPP version 2 was similar to the global worldwide prevalence - yet at the upper end. STOPP version 2 was more successful than Beers 2012 to detect PIM. Patients with multiple drug use, multiple comorbidities and more dependency were more likely to have PIM requiring special attention during prescription. Geriatr Gerontol Int 2017; 17: 1245-1251.
Keywords: Beers 2012; comparison; potentially inappropriate prescribing; Screening Tool of Older Person's Prescriptions version 2; ADVERSE DRUG EVENTS; ELDERLY-PATIENTS; STOPP CRITERIA; ALERT DOCTORS; MEDICATIONS; POLYPHARMACY; RISK